Effects of Genetic and Environmental Factors on Aggregation Behaviors of Red Flour Beetles - Beauchamp, Madison; Marshall, Jeremy (My University, 2018)
Red Flour Beetles (Tribolium castaneum; Coleoptera: Tenebrionidae), are often used for ethological and food safety research due to an adept ability to colonize food sources. Red Flour Beetles and their relatives are a worldwide pest of stored products such as grains and are considered the most common secondary pests of all stored plant commodities throughout the world by the United Nations. Red Flour Beetles can live up to 3 years reproducing in a polygamous manner and can disperse through flight or cursorial movement. Important factors such as genetic makeup and interaction with the environment most certainly affect the beetles reproductive, colonizing, and feeding behaviors. The effects of these factors on the aggregational behaviors of these beetles is however extremely unexplored, and much more research is needed to better understand these important interactions
Keywords: Fall 2018